Studi Lanjutan Sebagai Alasan Perceraian di Pengadilan Agama Ambon dan Raha - Reffa Rahmanayla Triyandani; Witia Oktaviani (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The increasing participation of women in higher education often intersects with patriarchal norms and triggers domestic conflicts leading to divorce. Indonesian positive law does not explicitly regulate higher education as a ground for divorce; however, judicial practice demonstrates that education frequently appears within the context of marital breakdown. This study examines judicial considerations in the Decisions of the Religious Court of Ambon No. 242/Pdt.G/2020/PA.Ab and the Religious Court of Raha No. 0357/Pdt.G/2020/PA.Rh through normative research using a case approach, focusing on the basis of judicial reasoning, statutory interpretation, and the application of the maqashid al-shari’ah perspective. The findings indicate that higher education is not treated as an independent legal ground for divorce, but rather as a social context accompanying objectively proven marital breakdown, including prolonged separation, loss of communication, failure to fulfill marital obligations, and abandonment. Judges applied extensive and teleological interpretations of Article 19 letters (b) and (f) of Government Regulation No. 9 of 1975 in conjunction with Article 116 letters (b) and (f) of the Compilation of Islamic Law, reflecting a no-fault divorce approach that emphasizes the failure of marital functions rather than fault-based reasoning. A disparity in systematic interpretation is identified: the Religious Court of Ambon emphasizes the failure of marital objectives through a legal-formal approach, while the Religious Court of Raha prioritizes the protection of the wife through a gender-responsive, legal-substantive approach. From the perspective of maqāṣid al-sharīʿah, divorce in cases involving higher education is justified to safeguard the five essential objectives of Islamic law and to prevent greater harm than maintaining a disharmonious marriage.